Addition of Aegilops U and M Chromosomes Affects Protein and Dietary Fiber Content of Wholemeal Wheat Flour - Rakszegi, Marianna; Molnár, István; Lovegrove, Alison; Darkó, Éva; Farkas, András; Láng, László; Bedő, Zoltán; Doležel, Jaroslav; Molnár-Láng, Márta; Shewry, Peter (Frontiers in Plant Science, 2017)
Cereal grain fiber is an important health-promoting component in the human diet. One option to improve dietary fiber content and composition in wheat is to introduce genes from its wild relatives Aegilops biuncialis and Aegilops geniculata. This study showed that the addition of chromosomes 2Ug, 4Ug, 5Ug, 7Ug, 2Mg, 5Mg and 7Mg of Ae. geniculata and 3Ub, 2Mb, 3Mb and 7Mb of Ae. biuncialis into bread wheat increased the seed protein content. Chromosomes 1Ug and 1Mg increased the proportion of polymeric glutenin proteins, while the addition of chromosomes 1Ub and 6Ub led to its decrease. Both Aegilops species had higher proportions of β-glucan compared to arabinoxylan than wheat lines, and elevated β-glucan content was also observed in wheat chromosome addition lines 5U, 7U and 7M. The arabinoxylan content in wheat was increased by the addition of chromosomes 5Ug, 7Ug and 1Ub while water-soluble arabinoxylan was increased by the addition of chromosomes 5U, 5M and 7M, and to a lesser extent by chromosomes 3, 4, 6Ug and 2Mb. Chromosomes 5Ug and 7Mb also affected the structure of wheat arabinoxylan, as shown by the pattern of oligosaccharides released by digestion with endoxylanase. These results will help to map genomic regions responsible for edible fiber content in Aegilops and will contribute to the efficient transfer of wild alleles in introgression breeding programs to obtain wheat varieties with improved health benefits.